Author Correction: BCAT1 restricts αKG levels in AML stem cells leading to IDHmut -like DNA hypermethylation - Raffel, Simon; Lutz, Christoph; Poschet, Gernot; Jensen, Patrizia; Fröhling, Stefan; Wuchter, Patrick; Lichter, Peter; Hell, Rüdiger; Herrmann, Carl; Ho, Anthony Dick; Krijgsveld, Jeroen (Nature, 2018)
In Extended Data Fig. 1a of this Letter, the flow cytometry plot depicting the surface phenotype of AML sample DD08 was a duplicate of the plot for AML sample DD06. Supplementary Data 4 has been added to the Supplementary Information of the original Letter to clarify the proteome data acquisition and presentation. The original Letter has been corrected online.
Im Titel ist "mut" bei IDH hochgestellt
Gesehen am 22.05.2020